Parallel Texts and their Implicit Semantics in Baddi Ibno Al-Murabiti's Novel "Valleys of Thirst" - Kribaa, Nassima (Milev Journal of Research and Studies, 2022)
The contemporary Arab novel recorded a striking and competitive presence for the rest of the literary genres in keeping pace with political, cultural and social events and focusing on the depth of intellectual issues that take a human nature in general, and pertain to the Arab countries in particularAfter a number of novelists who renewed and rebelled against the usual and ready-made templates and wrote narrative texts focusing on what the parallel texts add to the narrative texts of hidden meanings, connotations and symbols. The main title of the novel, its cover, the titles of the novel's chapters and the textual thresholds will guide critical readings, as it is absolutely impossible to ignore its interpretive role. This can be seen in the novel "Valleys of Thirst" by the Mauritanian novelist "Baddy Ibno Al-Murabiti", where parallel texts with their intellectual, political and mythological dimensions appear to expose the miserable reality and expose the images that the regimes hide in.